Insights of Chinese herbal medicine for mitochondrial dysfunction in chronic cerebral hypoperfusion induced cognitive impairment: Existed evidences and potential directions - Wang, Yefei; Wang, Ying; Li, Shixin; Jin, Huihui; Duan, Jiayu; Lu, Xiyue; Qin, Yinglin; Song, Jiale; Li, Xiaoshan; Jin, Xianglan (Frontiers in Pharmacology, 2023)
Chronic cerebral hypoperfusion (CCH) is one of the main pathophysiological markers of cognitive impairment in central nervous system diseases. Mitochondria are cores of energy generation and information process. Mitochondrial dysfunction is the key upstream factors of CCH induced neurovascular pathology. Increasing studies explored the molecular mechanisms of mitochondrial dysfunction and self-repair for effective targets to improve CCH-related cognitive impairment. The clinical efficacy of Chinese herbal medicine in the treatment of CCH induced cognitive impairment is definite. Existed evidences from pharmacological studies have further proved that, Chinese herbal medicine could improve mitochondrial dysfunction and neurovascular pathology after CCH by preventing calcium overload, reducing oxidative stress damage, enhancing antioxidant capacity, inhibiting mitochondria-related apoptosis pathway, promoting mitochondrial biogenesis and preventing excessive activation of mitophagy. Besides, CCH mediated mitochondrial dysfunction is one of the fundamental causes for neurodegeneration pathology aggravation. Chinese herbal medicine also has great potential therapeutic value in combating neurodegenerative diseases by targeting mitochondrial dysfunction.